A moF-based anisotropic aerogel material and a preparation method thereof

CN122898147APending Publication Date: 2026-10-13GUIZHOU AEROSPACE WUJIANG MACHINERY & ELECTRICITYEQUIP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610788434.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

现有复合方式多为MOF与导热填料的机械共混,MOF颗粒易团聚、堵塞导热通路

Benefits of technology

1.打破了导热与隔热的矛盾:实现了面内高导热(2.0-8.0 W/(m·K))与面外高隔热(≤0.05 W/(m·K))在同材料中的高度统一,各向异性系数大于50。在快速导出局部热点的同时,有效阻挡热量穿透。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898147A_ABST
    Figure CN122898147A_ABST
Patent Text Reader

Abstract

The application discloses a MOF-based anisotropic aerogel material and a preparation method thereof. The aerogel material is integrally constructed by cellulose nanofibers, graphene oxide nanosheets and UiO-66 metal organic framework through an in-situ compounding process, has layered channels formed by directional freezing, and the layer wall is formed by the lapping of the cellulose nanofibers and the graphene oxide nanosheets, and the UiO-66 crystals are embedded in the layer wall. The preparation method comprises the following steps: preparing a homogeneous compounding slurry, carrying out a solvothermal reaction to make the UiO-66 nucleate and grow in-situ, replacing the solvent, unidirectional freezing, and synchronously completing the activation of the UiO-66 through supercritical carbon dioxide drying. The in-plane thermal conductivity of the obtained material is 2.0-8.0 W / (m.K), the out-of-plane thermal conductivity is less than or equal to 0.050 W / (m.K), and the anisotropy coefficient is greater than 50. The application realizes the synergistic optimization of the in-plane high thermal conductivity and the out-of-plane high heat insulation, and can be used for the thermal runaway protection of power batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanoporous composite materials and thermal management technology, specifically relating to a MOF-based anisotropic aerogel composite material with high in-plane thermal conductivity and high out-of-plane thermal insulation, and its preparation method. Background Technology

[0002] When lithium-ion batteries and other electrochemical energy storage devices are used in groups, thermal runaway of a single cell can easily lead to thermal propagation to adjacent cells, causing serious safety accidents. An ideal cell thermal separator needs to possess both "high in-plane thermal conductivity" to quickly dissipate hot spots on the cell surface and "ultra-low out-of-plane insulation" to block the propagation of thermal runaway. Traditional solutions often use a simple mixture of phase change materials or ceramic fiber felt with thermally conductive fillers, which makes it difficult to achieve extreme anisotropy of thermal conductivity and insulation in a single material.

[0003] Metal-organic frameworks (MOFs) have emerged as a promising new option for thermal insulation materials due to their ultra-high porosity and tunable structure. However, the integrated construction and anisotropy of MOFs with high thermal conductivity networks remain challenging. Current composite methods often involve the mechanical blending of MOFs with thermally conductive fillers, which can lead to MOF particle agglomeration and blockage of thermal conductivity pathways. Furthermore, MOFs typically require prolonged activation with toxic solvents after synthesis to restore their specific surface area. Therefore, leveraging the multifunctional properties of MOFs to synergistically achieve high thermal conductivity and high insulation within a single material system, while constructing a robust, integrated structure, is a pressing technological challenge. Summary of the Invention

[0004] The purpose of this invention is to provide a MOF-based anisotropic thermally conductive and insulating aerogel composite material, which achieves synergistic optimization of in-plane thermal conductivity and out-of-plane thermal insulation through in-situ composite and directional structural regulation of cellulose nanofibers, graphene oxide, and UiO-66. A method for preparing this composite material is also provided, cleverly combining supercritical drying and MOF activation to simplify the process. Ultimately, the material is applied to the thermal runaway protection of electrochemical energy storage devices.

[0005] To achieve the above-mentioned technical objectives, the present invention adopts the following technical solution: On one hand, the present invention provides a MOF-based anisotropic aerogel material, wherein the aerogel material is integrally constructed from cellulose nanofibers, graphene oxide nanosheets and UiO-66 metal-organic framework through an in-situ composite process; it has layered channels formed by directional freezing; the layer walls of the layered channels are composed of overlapping cellulose nanofibers and graphene oxide nanosheets, and the UiO-66 crystals are embedded in the layer walls.

[0006] The aerogel material has an in-plane thermal conductivity of 2.0–8.0 W / (m·K) along the orientation direction of the layered pores, an out-of-plane thermal conductivity ≤0.050 W / (m·K) perpendicular to the orientation direction of the layered pores, and an anisotropy coefficient greater than 50.

[0007] On the other hand, the present invention provides a method for preparing the above-mentioned MOF-based anisotropic aerogel material, comprising the following steps: S1. Preparation of homogeneous composite slurry: Aqueous dispersion of graphene oxide nanosheets and aqueous dispersion of cellulose nanofibers are mixed evenly, then zirconium source is added to dissolve, and then terephthalic acid organic ligand is added. The mixture is stirred evenly to obtain homogeneous slurry. S2. In-situ growth of metal-organic frameworks: The homogeneous slurry obtained in step S1 is subjected to a solvothermal reaction, so that UiO-66 crystals are grown in situ through nucleation in the cellulose nanofiber / graphene oxide network to obtain a wet gel. S3. Solvent replacement: The wet gel obtained in step S2 is subjected to solvent replacement; S4. Directional freezing: The wet gel after solvent replacement in step S3 is placed in a mold with a cold source at the bottom for unidirectional freezing to form a frozen preform with an anisotropic structure; S5. Drying and Simultaneous Activation: The frozen preform obtained in step S4 is dried with supercritical carbon dioxide. During the drying process, the UiO-66 crystals are activated simultaneously to obtain MOF-based anisotropic aerogel material.

[0008] Further, in step S1, the mass ratio of the graphene oxide nanosheets to the cellulose nanofibers is 1:0.5 to 1:2, the mass ratio of the graphene oxide nanosheets to the zirconium source is 1:0.5 to 1:3, and the molar ratio of the zirconium source to terephthalic acid is 1:1.

[0009] Furthermore, in step S1, the concentration of the aqueous dispersion of graphene oxide nanosheets is 5 mg / mL, and the concentration of the aqueous dispersion of cellulose nanofibers is 3 mg / mL; the mass ratio of graphene oxide nanosheets to cellulose nanofibers is 1:1, and the mass ratio of graphene oxide nanosheets to zirconium source is 1:1.2.

[0010] Further, in step S2, the temperature of the solvothermal reaction is 100–130°C, and the time is 12–36 hours. Preferably, the temperature is 120°C, and the time is 24 hours.

[0011] Further, in step S3, the solvent replacement involves washing the wet gel with deionized water to remove unreacted substances, followed by replacement with anhydrous ethanol 2 to 3 times.

[0012] Furthermore, in step S4, the temperature of the cold source for the unidirectional freezing is -20°C to -80°C, and the cooling rate is 0.5 to 2°C / min.

[0013] Further, in step S5, the supercritical carbon dioxide drying temperature is 40–60°C, the pressure is 10–25 MPa, and the time is 4–12 hours. Preferably, the temperature is 50°C, the pressure is 15 MPa, and the time is 8 hours.

[0014] Furthermore, the preparation method also includes step S6. Thermal conversion: the aerogel dried in step S5 is calcined at 600-1000℃ under an inert atmosphere to convert UiO-66 crystals in situ into porous carbon containing zirconium dioxide nanoparticles.

[0015] Furthermore, in step S6, the calcination temperature is 800°C, the heating rate is 5°C / min, and the holding time is 2 hours.

[0016] Compared with the prior art, the present invention has the following significant advantages: 1. It breaks the contradiction between thermal conductivity and thermal insulation: It achieves a high degree of uniformity between high in-plane thermal conductivity (2.0-8.0 W / (m·K)) and high out-of-plane thermal insulation (≤0.05 W / (m·K)) in the same material, with an anisotropy coefficient greater than 50. While rapidly dissipating local hot spots, it effectively blocks heat penetration.

[0017] 2. Low interfacial thermal resistance and high thermal management efficiency: Since the MOF (UiO-66 metal-organic framework) is directly nucleated and grown on the surface of graphene oxide nanosheets, compared to the mechanical mixing of metal-organic frameworks and thermally conductive fillers in existing technologies, the in-situ growth method of this invention significantly reduces phonon scattering between the filler and the matrix, thus lowering the interfacial thermal resistance. Simultaneously, cellulose nanofibers, acting as a "green dispersant," prevent the stacking of graphene oxide nanosheets, maximizing the integrity of the in-plane long-range thermal conductivity pathways, thereby achieving excellent in-plane thermal conductivity.

[0018] 3. Interfacial self-reinforcing and high flexibility: In-situ growth of MOFs creates an "anchoring" effect between cellulose nanofibers and graphene oxide nanosheets, significantly enhancing interfacial bonding. The resulting aerogel material does not crack after repeated bending, can adapt to the expansion stress during the charging and discharging process of the battery cell, and exhibits good mechanical flexibility and structural stability.

[0019] 4. Wide application window and thermally induced passive response: This invention can undergo thermal conversion treatment according to application requirements: the dried aerogel is calcined in an inert atmosphere, and the MOF is converted in situ into porous carbon containing zirconium dioxide nanoparticles. The out-of-plane thermal conductivity can be further reduced to 0.020-0.040 W / (m·K), and the upper limit of the applicable temperature is increased from about 350℃ to over 800℃. The material after thermal conversion exhibits intelligent passive safety characteristics with enhanced thermal insulation performance as the temperature increases, making it suitable for thermal management in high-temperature scenarios.

[0020] 5. Simplified and Environmentally Friendly Preparation Process: This invention combines supercritical carbon dioxide drying and MOF activation into one step. During the drying process, residual solvent within the metal-organic framework pores is extracted simultaneously, achieving both drying and activation in one step. This avoids the prolonged immersion in toxic solvents or high-temperature vacuum activation steps required in traditional metal-organic framework activation, simplifying the process, shortening the preparation cycle, and making it more environmentally friendly. Furthermore, supercritical carbon dioxide drying completely preserves the anisotropic layered structure formed by directional freezing, avoiding the pore collapse problem that can occur with freeze-drying. Attached Figure Description

[0021] The present invention will now be described with reference to the accompanying drawings.

[0022] Figure 1 This is a schematic diagram of the preparation method of the composite aerogel of the present invention.

[0023] Figure 2 This is a comparison diagram of the density gradient distribution at different positions along the directional freezing direction of the composite aerogels prepared in Example 1 and the comparative example of the present invention.

[0024] Figure 3 This is a comparison chart showing the in-plane and out-of-plane thermal conductivity test results of the composite aerogels prepared in Example 1 and the comparative example of the present invention.

[0025] Figure 4 This is a comparison chart showing the joint verification of BET specific surface area and in-plane thermal conductivity of the composite aerogels prepared in Example 1 and the comparative example of the present invention. Detailed Implementation

[0026] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example 1

[0027] like Figure 1As shown, the preparation method of the MOF-based anisotropic aerogel composite material in this embodiment includes steps S1 to S5. The specific steps are as follows: S1. Preparation of homogeneous composite slurry: Aqueous dispersions of graphene oxide nanosheets (GO) (5 mg / mL) and cellulose nanofibers (CNF) (3 mg / mL) were mixed at a mass ratio of 1:1. The mixture was ultrasonically stirred for 1 hour until uniformly dispersed. Then, zirconium tetrachloride (ZrCl4) was added to the above mixed dispersion at a mass ratio of 1:1.2 and stirred until completely dissolved. Finally, an equimolar amount of terephthalic acid was added to the above solution, and stirring was continued for 30 minutes to obtain a homogeneous slurry.

[0028] S2. In-situ growth of metal-organic frameworks: The homogeneous slurry obtained in step S1 was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, sealed, and placed in an oven for solvothermal reaction at 120°C for 24 hours. After the reaction, it was naturally cooled to room temperature, and the reactor was removed to obtain an in-situ grown wet gel of cellulose nanofibers / graphene oxide / UiO-66. In this process, UiO-66 crystals use the oxygen-containing functional groups on the surface of graphene oxide nanosheets as nucleation sites, and grow in situ within the cellulose nanofibers / graphene oxide network to form a stable three-dimensional network structure.

[0029] S3. Solvent Replacement: Remove the wet gel obtained in step S2 from the reactor and soak it in deionized water for 24 hours, changing the deionized water 2-3 times during this period to remove unreacted raw materials and byproducts. Then, replace the water in the wet gel with anhydrous ethanol three times, each replacement lasting 12 hours. Specifically, immerse the wet gel in anhydrous ethanol, replacing the ethanol with fresh anhydrous ethanol every 12 hours, for a total of three replacements.

[0030] S4. Directional Freezing: The wet gel after solvent replacement in step S3 is placed in a mold with a cold source at the bottom. The bottom of the mold is in contact with the cold source, which in this embodiment is set to -60°C, creating a unidirectional temperature gradient from bottom to top within the mold. Unidirectional freezing is performed at a cooling rate of 2°C / min. During this process, the solvent water in the wet gel grows directionally into ice crystals along the temperature gradient (from bottom to top), while the solute (cellulose nanofibers, graphene oxide nanosheets, and UiO-66 crystals embedded within them) is displaced between the ice crystals, forming an anisotropically arranged frozen preform. After the wet gel has completely solidified, a frozen preform with an anisotropic structure is obtained.

[0031] S5. Drying and Simultaneous Activation: The frozen preform obtained in step S4 was transferred to a supercritical carbon dioxide drying apparatus. The drying temperature was set to 50℃, the pressure to 15 MPa, and the drying time to 8 hours. Under supercritical carbon dioxide conditions, the ice crystals in the frozen preform directly sublimated, leaving behind a directionally arranged layered pore structure, forming an aerogel. Simultaneously, supercritical carbon dioxide, with its excellent mass transfer properties and low surface tension, effectively penetrated into the nanopores of the UiO-66 crystals, extracting residual solvents (water, ethanol, etc.) from the pores. This process simultaneously activated the UiO-66 crystals, restoring their high specific surface area and porous structure. After drying, the pressure was slowly released, and the sample was removed, yielding the MOF-based anisotropic aerogel material.

[0032] The aerogel material prepared in this embodiment has an in-plane thermal conductivity of 3.2 W / (m·K), an out-of-plane thermal conductivity of 0.042 W / (m·K), an anisotropy coefficient of 76, a BET specific surface area of ​​836 m² / g, and a density gradient of 15–60 mg / cm³ along the directional freezing direction (distributed in a gradient). Example 2

[0033] This embodiment is basically the same as Embodiment 1, except for the freezing rate in step S4 (directional freezing).

[0034] In this embodiment, step S4 is specifically performed as follows: The wet gel after solvent replacement in step S3 is placed in a mold with a cold source at the bottom. In this embodiment, the temperature of the cold source is set to -60℃, so that a unidirectional temperature gradient is formed from the bottom to the top inside the mold. Unidirectional freezing is performed at a cooling rate of 0.5℃ / min. After the wet gel is completely solidified, a frozen preform with an anisotropic structure is obtained.

[0035] The other steps S1, S2, S3, and S5 are the same as in Example 1.

[0036] The aerogel material prepared in this embodiment has an in-plane thermal conductivity of 4.5 W / (m·K), an out-of-plane thermal conductivity of 0.029 W / (m·K), and an anisotropy coefficient of 155. It can be concluded that when the freezing rate is reduced to 0.5℃ / min, ice crystal growth is more complete and orderly, resulting in a more regular layered pore structure. Therefore, the in-plane thermal conductivity increases, the out-of-plane thermal conductivity further decreases, and the anisotropy coefficient significantly increases. Example 3

[0037] This embodiment adds a thermal conversion step (step S6) to the existing embodiment 1.

[0038] S6. Thermal conversion: The aerogel dried in step S5 of Example 1 was placed in a tube furnace, and after evacuation, argon gas was introduced as a protective atmosphere. The temperature was increased to 800°C at a heating rate of 5°C / min, held for 2 hours, and then naturally cooled to room temperature.

[0039] Under a high-temperature inert atmosphere, cellulose nanofibers and graphene oxide nanosheets undergo pyrolysis, transforming into porous carbon matrix materials. UiO-66 crystals are also transformed in situ into porous carbon containing zirconium dioxide nanoparticles during pyrolysis. In the resulting product, zirconium dioxide nanoparticles are uniformly dispersed within the porous carbon matrix, forming a composite material with a hierarchical porous structure.

[0040] The other steps S1 to S5 are the same as in Example 1.

[0041] In this embodiment, the out-of-plane thermal conductivity of the aerogel material after thermal conversion is 0.032 W / (m·K), and the upper limit of its applicable temperature is increased from approximately 350°C for the original aerogel to over 800°C. This thermally converted material is particularly suitable for thermal management applications in high-temperature scenarios, such as high-temperature battery systems or thermal protection in the aerospace field.

[0042] Comparative Example The preparation method of the physical blending control group sample in the comparative example is as follows: (1) First, UiO-66 crystal powder was synthesized separately. The synthesis conditions were as follows: zirconium tetrachloride and terephthalic acid were dissolved in N,N-dimethylformamide at a molar ratio of 1:1 and reacted at 120°C for 24 hours. After centrifugation, washing and drying, UiO-66 crystal powder was obtained.

[0043] (2) Mix the aqueous dispersion of graphene oxide nanosheets (concentration 5 mg / mL) and the aqueous dispersion of cellulose nanofibers (concentration 3 mg / mL) at a mass ratio of 1:1 and then ultrasonically disperse for 1 hour.

[0044] (3) According to the mass ratio of graphene oxide nanosheets to UiO-66 crystals of 1:1.2, the pre-synthesized UiO-66 crystal powder was added to the above mixed dispersion and ultrasonically dispersed for 30 minutes to obtain a physical blend slurry.

[0045] (4) The physical blend slurry was treated according to the same steps as in Example 1: S3 (solvent replacement), S4 (directional freezing), and S5 (supercritical carbon dioxide drying and synchronous activation) to obtain the physical blend control group aerogel sample.

[0046] The aerogel samples prepared by the physically blended control group had an in-plane thermal conductivity of 1.3 W / (m·K), an out-of-plane thermal conductivity of 0.28 W / (m·K), an anisotropy coefficient of 4.6, a BET specific surface area of ​​412 m² / g, and a density gradient of 36–40 mg / cm³ along the directional freezing direction (without a significant gradient). This is because the UiO-66 crystals in the physically blended slurry were pre-synthesized and agglomerated, which disrupted the growth of ice crystals during directional freezing, preventing the formation of regular layered channels. Consequently, the solute was not directionally displaced, resulting in a uniform density distribution along the freezing direction without a significant gradient.

[0047] Based on the above embodiments and comparative examples, the performance test results of the various aerogel materials prepared by the present invention are summarized in the following table: Table 1 Performance Comparison of Various Embodiments and Comparative Examples

[0048] Note: "—" indicates that the indicator was not tested.

[0049] As can be seen from the table above: (1) In-plane thermal conductivity: such as Figure 2 and Figure 3 As shown, the thermal conductivity of Example 1 (3.2 W / (m·K)) and Example 2 (4.5 W / (m·K)) was significantly higher than that of the comparative example (1.3 W / (m·K)). This is because the present invention uses an in-situ growth process, where UiO-66 crystals are directly grown on the surface of graphene oxide nanosheets, resulting in tight interfacial bonding, reduced phonon scattering, and effective prevention of graphene oxide nanosheet stacking by cellulose nanofibers, ensuring the integrity of the in-plane thermal conductivity pathways. In contrast, the physical mixing method results in a large interfacial thermal resistance between the UiO-66 crystals and graphene oxide nanosheets, and the random distribution of UiO-66 crystals partially blocks the thermal conductivity pathways of graphene oxide.

[0050] (2) Out-of-plane thermal conductivity: The out-of-plane thermal conductivity of Example 1 (0.042 W / (m·K)) and Example 2 (0.029 W / (m·K)) is much lower than that of the comparative example (0.28 W / (m·K)). This is because the present invention uses directional freezing to construct anisotropic layered channels, and the interlayer pores effectively block the transfer of heat to the out-of-plane direction; while physical mixing methods cannot form a regular layered structure, have a high degree of isotropy, and poor out-of-plane thermal insulation performance.

[0051] (3) Anisotropy coefficient: Both Example 1 (76) and Example 2 (155) are much higher than Comparative Example (4.6), which fully demonstrates that the present invention has successfully achieved extreme anisotropy of thermal conductivity.

[0052] (4) BET specific surface area: such as Figure 4As shown, Example 1 (836 m² / g) is approximately twice that of the comparative example (412 m² / g). This is because the supercritical carbon dioxide drying and simultaneous activation process of the present invention simultaneously extracts the residual solvent within the pores of UiO-66 during the drying process, effectively activating the pore structure of UiO-66; while in the physical blending control group, although the UiO-66 crystals had undergone conventional activation after being synthesized alone, some pores may have been re-blocked or collapsed after subsequent directional freezing and drying processes.

[0053] (5) After thermal conversion, the out-of-plane thermal conductivity of Example 3 is further reduced to 0.032 W / (m·K), and the upper limit of applicable temperature is increased to over 800℃, making it particularly suitable for thermal management applications in high-temperature scenarios.

[0054] Other aspects of this invention that are not detailed herein are all conventional techniques known to those skilled in the art.

[0055] It should be noted that the terms “comprising,” “including,” or any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0056] The scope of protection of this invention is not limited to the technical solutions disclosed in the specific embodiments. Any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of this invention shall fall within the scope of protection of this invention.

Claims

1. A MOF-based anisotropic aerogel material, characterized in that: The aerogel material is integrally constructed from cellulose nanofibers, graphene oxide nanosheets, and UiO-66 metal-organic framework through an in-situ composite process; it has layered channels formed by directional freezing; the walls of the layered channels are composed of overlapping cellulose nanofibers and graphene oxide nanosheets, and the UiO-66 crystals are embedded in the layer walls.

2. A method for preparing the MOF-based anisotropic aerogel material according to claim 1, characterized in that: S1. Preparation of homogeneous composite slurry: Aqueous dispersion of graphene oxide nanosheets and aqueous dispersion of cellulose nanofibers are mixed evenly, then zirconium source is added to dissolve, and then terephthalic acid organic ligand is added. The mixture is stirred evenly to obtain homogeneous slurry. S2. In-situ growth of metal-organic frameworks: The homogeneous slurry obtained in step S1 is subjected to a solvothermal reaction, so that UiO-66 crystals are grown in situ through nucleation in the cellulose nanofiber / graphene oxide network to obtain a wet gel. S3. Solvent replacement: The wet gel obtained in step S2 is subjected to solvent replacement; S4. Directional freezing: The wet gel after solvent replacement in step S3 is placed in a mold with a cold source at the bottom for unidirectional freezing to form a frozen preform with an anisotropic structure; S5. Drying and Simultaneous Activation: The frozen preform obtained in step S4 is dried with supercritical carbon dioxide. During the drying process, the UiO-66 crystals are activated simultaneously to obtain MOF-based anisotropic aerogel material.

3. The method for preparing MOF-based anisotropic aerogel material according to claim 2, characterized in that: In step S1, the mass ratio of graphene oxide nanosheets to cellulose nanofibers is 1:0.5 to 1:2, the mass ratio of graphene oxide nanosheets to zirconium source is 1:0.5 to 1:3, and the molar ratio of zirconium source to terephthalic acid is 1:

1.

4. The method for preparing MOF-based anisotropic aerogel material according to claim 3, characterized in that: In step S1, the concentration of the aqueous dispersion of graphene oxide nanosheets is 5 mg / mL, and the concentration of the aqueous dispersion of cellulose nanofibers is 3 mg / mL; the mass ratio of graphene oxide nanosheets to cellulose nanofibers is 1:1, and the mass ratio of graphene oxide nanosheets to zirconium source is 1:1.

2.

5. The method for preparing MOF-based anisotropic aerogel material according to claim 2, characterized in that: In step S2, the temperature of the solvothermal reaction is 100–130°C, and the time is 12–36 hours.

6. The method for preparing MOF-based anisotropic aerogel material according to claim 2, characterized in that: In step S3, the solvent replacement involves washing the wet gel with deionized water to remove unreacted substances, followed by replacement with anhydrous ethanol 2 to 3 times.

7. The method for preparing MOF-based anisotropic aerogel material according to claim 2, characterized in that: In step S4, the temperature of the cold source for the unidirectional freezing is -20°C to -80°C, and the cooling rate is 0.5 to 2°C / min.

8. The method for preparing MOF-based anisotropic aerogel material according to claim 2, characterized in that: In step S5, the temperature for supercritical carbon dioxide drying is 40–60°C, the pressure is 10–25 MPa, and the time is 4–12 hours.

9. The method for preparing MOF-based anisotropic aerogel material according to claim 2, characterized in that: It also includes step S6. Thermal conversion: the aerogel dried in step S5 is calcined at 600-1000℃ in an inert atmosphere to convert UiO-66 crystals in situ into porous carbon containing zirconium dioxide nanoparticles.

10. The method for preparing MOF-based anisotropic aerogel material according to claim 9, characterized in that: In step S6, the calcination temperature is 800℃, the heating rate is 5℃ / min, and the holding time is 2 hours.